Mixed positive electrode for solid-state battery, corresponding battery and preparation method
By introducing a mixed preparation method of iodine-containing materials and lithium-battery positive electrode materials into the positive electrode of solid-state battery, the problem of insufficient electrochemical performance of solid-state batteries is solved, the cycle rate and charge transfer efficiency of the battery are improved, and stability under high load conditions is achieved Operation and electrochemical performance improvements.
Patent Information
- Application Number
- CN202411418459.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-10-11
AI Technical Summary
Solid-state lithium batteries are not as good as liquid lithium-ion batteries in terms of energy and power density, and the ion transmission efficiency of the solid positive electrode is low, resulting in unsatisfactory electrochemical performance, especially under high load conditions, the internal charge and mass transfer of the electrode is slow and the cycle rate performance is insufficient.
Iodine-containing materials are mixed with lithium battery positive electrode materials, and fine particles are formed by grinding and ball mill grinding. Combining conductive agents, binders and solvents, coating and drying in a vacuum environment to prepare a mixed positive electrode to improve ion transport and charge transfer efficiency.
It significantly improves the cycle rate performance and electrochemical performance of solid-state batteries, can operate stably under high load and appropriate current density, extends battery life and reduces costs, and is suitable for large-scale industrial applications.
Smart Images

Figure CN119230763A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of new energy batteries, and specifically relates to a method for preparing a mixed positive electrode for a solid-state battery, as well as a mixed positive electrode prepared by the method and a corresponding battery. Background Art
[0002] All-solid-state lithium batteries (ASSLBs) are promising energy storage devices, but their energy and power density are still inferior to those of lithium-ion batteries (LIBs) with liquid electrolytes (LEs). Although improving the ionic conductivity of solid electrolytes (SSEs) is the key to improving the performance of ASSLBs, it is still insufficient in the charge-mass transport throughout the battery. During battery operation, the ion permeation network in the composite cathode is crucial to maintain the electrochemical reaction of the cathode active materials (CAMs).
[0003] In conventional LIBs, the porous nature of the cathode enables LEs to penetrate easily, ensuring good ion transport. However, within the composite cathode, it is difficult for the SSE to establish a continuous ion transport channel, resulting in low CAM utilization and limited capacity output. In addition, there is a large energy barrier for lithium ions to transport across the interface, and incompatible solid-solid contacts and side reactions further increase the impedance and reduce the capacity retention. Therefore, to ensure high-performance ASSLBs, it is crucial to design the microstructure of the solid-state cathode to establish an efficient ion permeation network.
[0004] Although crystal structure control, surface modification, pore regulation, and ion conduction path optimization can provide additional ion diffusion pathways and help establish an efficient ion permeation network, these solid-state cathodes still face the problem of low CAM loading (usually less than 5 mg cm -2 ) and poor rate performance. For the practical application of ASSLBs, designing a composite cathode that can operate at high load and appropriate current density becomes a key issue that must be addressed. However, increasing the CAM load will bring performance limitations related to ion penetration in the solid-state cathode. Increasing the cathode thickness and / or shortening the charge and discharge interval will intensify the ion concentration gradient along the depth of the cathode, leading to increased polarization and insufficient CAM utilization. In view of the current problems of solid-state batteries with unsatisfactory electrochemical performance under higher load cathodes and slow charge and mass transfer inside the electrode.
[0005] Typical prior art records: Traditional lithium-ion battery cathode materials, such as lithium iron phosphate (LiFePO 4 ), ternary materials (NCM, NCA), etc., have been widely used in liquid electrolyte batteries. However, these materials show certain limitations in solid-state batteries. The main reason is that the interface resistance between the solid electrolyte and the positive electrode material is large, which affects the transmission efficiency of lithium ions.
[0006] J. Am. Chem. Soc. 2022, 144, 32, 14638–14646The application of iodide ion (I⁻) as an additive in liquid batteries has been studied to a certain extent, and can improve the electrochemical performance of batteries to a certain extent. For example, studies have shown that lithium iodide (LiI) can be used as an electrolyte additive to improve the cycle stability of lithium-ion batteries, but its application in solid-state battery positive electrodes has not been fully studied.
[0007] The prior art records the improvement of positive electrode performance by adding additives: CN202311665592.4, and some research works attempt to add conductive additives or ion conductors to the positive electrode materials to improve the overall performance of the battery. For example, adding conductive materials such as carbon nanotubes and graphene can improve the conductivity of the positive electrode, thereby improving the rate performance of the battery. The effect of these additives is limited, and increases the cost of the materials and the complexity of the preparation process.
[0008] Through the interface modification technology CN202210142540.8, by introducing an interface modification layer (such as coating a highly conductive film) at the interface between the solid electrolyte and the positive electrode material, the interface resistance can be effectively reduced and the transmission efficiency of lithium ions can be improved. This coating technology is costly and difficult to promote on a large scale.
[0009] CN201910385205.9 proposes composite positive electrode materials to synergistically improve battery performance. For example, lithium iron phosphate is compounded with lithium cobalt oxide to utilize the safety of the former and the high energy density of the latter. Although this method improves battery performance to a certain extent, it is still insufficient in improving cycle rate performance, and material selection and composite process require careful control.
[0010] The present invention aims to provide a hybrid positive electrode for solid-state batteries, a corresponding battery and a preparation method that can promote charge transfer inside the electrode, effectively promote the transmission of lithium ions, and effectively improve the cycle rate performance of solid-state batteries. The preparation method is simple and suitable for large-scale industrial applications. Summary of the invention
[0011] In order to overcome the problems of insufficient battery performance, complex preparation process and high cost of existing solid-state batteries, the present application proposes a hybrid positive electrode for a solid-state battery, a corresponding battery and a preparation method.
[0012] In a first aspect, the present invention provides a method for preparing a hybrid positive electrode for a solid-state battery, the synthesis method comprising the following steps: (1) selecting an iodine-containing material A1 and a lithium battery positive electrode material A2 with a predetermined content; A1 and A2 are mixed to obtain mixed material A.
[0013] Furthermore, the iodine-containing material A1 is one or more of methylamine hydroiodide, tetrabutylammonium triiodide, imidazole hydroiodide, 1-iodoferrocene, iodinated polyacrylonitrile, lithium iodide, sodium iodide, potassium iodide, and methyl iodide; the lithium battery positive electrode material A2 is one or more of lithium iron phosphate, lithium manganese iron phosphate, lithium nickel cobalt manganate, lithium manganate, etc.; the mass ratio of the iodine-containing material A1 to the lithium battery positive electrode material A2 is 0.1~10.
[0014] (2) Grind the mixture A in an agate mortar and mix it evenly to form fine particles to obtain a mixed material C.
[0015] Furthermore, the mixture A in step (2) is ground in the agate mortar for 1-6 hours.
[0016] (3) Grind the mixed material C, conductive agent D, binder E, and solvent F in a ball mill to obtain a mixed slurry G.
[0017] Furthermore, the grinding time in step (3) is 1-6 hours.
[0018] (4) The mixed slurry G is coated on the carbon-coated aluminum foil with a coating thickness of 10-100 μm.
[0019] (5) Drying the coated aluminum foil in a vacuum environment at a drying temperature of 50-110° C. to obtain an iodine-added mixed positive electrode.
[0020] Furthermore, the drying time in step (5) is 6-12 hours.
[0021] Furthermore, the conductive agent in step (3) is one or more of graphite, carbon nanotubes, acetylene black, and graphene.
[0022] Furthermore, the binder E in step (3) is one or more of polyvinylidene fluoride, styrene-butadiene rubber, carboxymethyl cellulose, polyacrylic acid, polyacrylonitrile, and polyacrylate.
[0023] Furthermore, the solvent in step (3) is one or more of N,N-dimethylformamide, acetonitrile, tetrahydrofuran, ethylene glycol dimethyl ether, N-methylpyrrolidone, anisole, dimethyl sulfoxide, and acetone.
[0024] Furthermore, the mass ratio of the mixed material C, the conductive agent D, and the binder E in step (1) is 8:1:1.
[0025] Furthermore, the ball milling is performed using a planetary ball mill at a rotation speed of 100-1000 r / min for 1-6 hours, preferably at a rotation speed of 200-800 r / min for 2-5 hours; at a rotation speed of 400-600 r / min for 4-6 hours.
[0026] In a second aspect, the present invention also provides a hybrid positive electrode for a solid-state battery, which is prepared by the method described in the first aspect.
[0027] In a third aspect, the present invention further provides a battery, comprising a negative electrode composed of the mixed positive electrode and lithium metal as described in the second aspect, and a polyethylene oxide solid electrolyte.
[0028] Furthermore, the battery can be stably cycled for at least 1000 times at a high rate of 2C in the test voltage range of 2.0-3.8 V, and can achieve a high surface capacity of 7.1 mg cm -2 And stable operation for at least 50 cycles at 0.1C rate.
[0029] The present invention has the following advantages: 1) The present invention improves the ion transport and charge transfer inside the solid-state battery hybrid positive electrode material by introducing iodine-containing materials, which is beneficial to comprehensively improve the electrochemical performance of the solid-state battery.
[0030] 2) The present invention introduces iodine-containing materials to prepare solid-state battery hybrid positive electrode materials, thereby improving the long cycle and rate performance of the solid-state battery composite positive electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 The SEM image of the mixed positive electrode containing iodine element material prepared in Example 2; Figure 2 The battery performance comparison cycle test chart of different examples; Figure 3 This is a long cycle test diagram of the solid-state battery of Example 2 at a high rate of 2C; Figure 4 This is a cycle test diagram of the solid-state battery under high load at 0.1C in Example 2; Figure 5 This is the electrochemical impedance test diagram of the mixed positive electrode of iodine-containing material and iodine-free material. DETAILED DESCRIPTION
[0032] For a better understanding of the present invention, the following examples are provided to further illustrate the present invention, but the content of the present invention is not limited to the following examples. Example 1
[0033] (1) Weigh the iodine-containing material lithium iodide and the lithium battery positive electrode material lithium iron phosphate in a mass ratio of 1:100, mix them in an agate mortar, and grind them for 30 minutes to obtain a mixed material A.
[0034] (2) Grind the mixed material A in an agate mortar for 4 hours to ensure that the materials are fully and evenly mixed to form fine particles, thereby obtaining a mixed material C.
[0035] (3) The mixed material C, the conductive agent acetylene black, the binder polyvinylidene fluoride, and the solvent N-methylpyrrolidone were ground in a ball mill at a mass ratio of 8:1:1:10 for 3 hours to obtain a mixed slurry G.
[0036] (4) The mixed slurry G was coated on the carbon-coated aluminum foil with a coating thickness of about 50 μm to ensure uniform distribution.
[0037] (5) Drying the coated aluminum foil in a vacuum environment at a drying temperature of 80° C. for 8 hours to ensure that the solvent is completely evaporated to obtain an iodine-added hybrid positive electrode.
[0038] (6) Polyethylene oxide and lithium trifluoromethylsulfonyl imide were weighed in a molar ratio of 16:1, dissolved in an appropriate amount of acetonitrile, and stirred at 60°C for 12 h until the slurry became viscous. The slurry was then poured into a polytetrafluoroethylene mold, transferred to a vacuum drying oven, and dried at 80°C for 12 h. After drying, the slurry was cut into pieces with a diameter of 16 mm using a cutting machine for later use, thereby obtaining a polyethylene oxide polymer solid electrolyte membrane.
[0039] (7) A lithium metal sheet is used as the negative electrode, the mixed positive electrode containing iodine element material prepared in steps 1-5 is used as the positive electrode, and the solid electrolyte membrane prepared in step 6 is used as the electrolyte. They are assembled into a 2025 type button-type solid-state battery in a super-purified glove box (water and oxygen content are all less than 0.1 ppm). Example 2
[0040] (1) The iodine-containing material methylamine hydroiodide and the lithium battery positive electrode material lithium iron phosphate were weighed in a mass ratio of 1:7 and mixed in an agate mortar and ground for 30 minutes to obtain a mixed material A.
[0041] (2) Grind the mixed material A in an agate mortar for 4 hours to ensure that the materials are fully and evenly mixed to form fine particles, thereby obtaining a mixed material C.
[0042] (3) The mixed material C, the conductive agent acetylene black, the binder polyvinylidene fluoride, and the solvent N-methylpyrrolidone were ground in a ball mill at a mass ratio of 8:1:1:20 for 6 hours to obtain a mixed slurry G.
[0043] (4) The mixed slurry G was coated on the carbon-coated aluminum foil with a coating thickness of about 25 μm to ensure uniform distribution.
[0044] (5) Dry the coated aluminum foil in a vacuum environment, usually at a temperature of 60°C for 12 hours, to ensure that the solvent is completely evaporated to obtain an iodine-doped mixed positive electrode.
[0045] (6) Polyethylene oxide and lithium trifluoromethylsulfonyl imide were weighed in a molar ratio of 16:1, dissolved in an appropriate amount of acetonitrile, and stirred at 60°C for 12 h until the slurry became viscous. The slurry was then poured into a polytetrafluoroethylene mold, transferred to a vacuum drying oven, and dried at 80°C for 12 h. After drying, the slurry was cut into pieces with a diameter of 16 mm using a cutting machine for later use, thereby obtaining a polyethylene oxide polymer solid electrolyte membrane.
[0046] (7) The other assembly steps of the solid-state battery are the same as those in Example 1. Example 3
[0047] (1) Weigh the iodine-containing material methylamine hydroiodide and the lithium battery positive electrode material lithium iron phosphate in a mass ratio of 100:1, mix them in an agate mortar, and grind them for 30 minutes to obtain a mixed material A.
[0048] (2) Grind the mixed material A in an agate mortar for 8 hours to ensure that the materials are fully and evenly mixed to form fine particles, thereby obtaining a mixed material C.
[0049] (3) The mixed material C, the conductive agent acetylene black, the binder polyvinylidene fluoride, and the solvent N-methylpyrrolidone were ground in a ball mill at a mass ratio of 8:1:1:5 for 10 hours to obtain a mixed slurry G.
[0050] (4) The mixed slurry G was coated on the carbon-coated aluminum foil with a coating thickness of about 15 μm to ensure uniform distribution.
[0051] (5) Dry the coated aluminum foil in a vacuum environment, usually at a drying temperature of 60°C for 12 hours, to ensure that the solvent is completely evaporated to obtain an iodine-added mixed positive electrode.
[0052] (6) Polyethylene oxide and lithium trifluoromethylsulfonyl imide were weighed in a molar ratio of 16:1, dissolved in an appropriate amount of acetonitrile, and stirred at 60°C for 12 hours until the slurry became viscous. The slurry was then poured into a polytetrafluoroethylene mold, transferred to a vacuum drying oven, and dried at 80°C for 12 hours. After drying, the slurry was cut into pieces with a diameter of 16 mm for later use, thereby obtaining a polyethylene oxide polymer solid electrolyte membrane.
[0053] (7) The other assembly steps of the solid-state battery are the same as those in Example 1. Comparative Example 1
[0054] (1) Weigh lithium iron phosphate, a positive electrode material of a lithium battery, and mix them in an agate mortar and grind them for 30 minutes to obtain a mixed material A.
[0055] (2) Grind the mixed material A in an agate mortar for 4 hours to ensure that the materials are fully and evenly mixed to form fine particles, thereby obtaining a mixed material C.
[0056] (3) The mixed material C, the conductive agent acetylene black, the binder polyvinylidene fluoride, and the solvent N-methylpyrrolidone were ground in a ball mill at a mass ratio of 8:1:1:20 for 6 hours to obtain a mixed slurry G.
[0057] (4) The mixed slurry G was coated on the carbon-coated aluminum foil with a coating thickness of about 25 μm to ensure uniform distribution.
[0058] (5) Dry the coated aluminum foil in a vacuum environment, usually at a temperature of 60°C for 12 hours, to ensure that the solvent is completely evaporated to obtain a hybrid positive electrode.
[0059] (6) Polyethylene oxide and lithium trifluoromethylsulfonyl imide were weighed in a molar ratio of 16:1, dissolved in an appropriate amount of acetonitrile, and stirred at 60°C for 12 h until the slurry became viscous. The slurry was then poured into a polytetrafluoroethylene mold, transferred to a vacuum drying oven, and dried at 80°C for 12 h. After drying, the slurry was cut into pieces with a diameter of 16 mm using a cutting machine for later use, thereby obtaining a polyethylene oxide polymer solid electrolyte membrane.
[0060] (7) The other assembly steps of the solid-state battery are the same as those in Example 1.
[0061] Performance Testing The 2025 button-type solid-state battery assembled with the mixed positive electrode prepared in Example 1, Example 2, and Example 3 was tested for its cycle performance on a blue battery tester, where the test voltage range was 2.0~3.8V, and the constant current charge and discharge test was performed at a rate of 0.5C. Figure 2 It can be seen that after 100 cycles, the battery of Example 2 has a discharge capacity of 2.9, 27.9, 165.6, and 2.8 mAh / g, respectively, compared with Examples 1, 2, 3, and Comparative Example 1. It can be seen that Example 2 has good cycle stability. In addition, the battery prepared in Example 2 can be stably cycled for 1000 times at a high rate of 2C, and can be used at a high surface capacity of 7.1 mg cm -2 Stable operation for 50 cycles at 0.1C rate.
[0062] Table 1 In addition, Figure 5The impedance test of the ion-electronic symmetrical battery is also used to test and calculate the ion / electronic conductivity of the mixed electrode. The results are shown in Table 1. The mixed positive electrode of Example 2 with the addition of iodine-containing material has greater ion and electronic conductivity than that of Comparative Example 1. This shows that adding an appropriate amount of iodine-containing material in the mixed positive electrode according to the present invention constructs fast lithium ion transmission and fast charge transfer inside the mixed positive electrode, thereby improving the long cycle and rate performance of the solid-state battery composite positive electrode.
[0063] The embodiments described above are only preferred technical solutions of the present invention and should not be regarded as limitations of the present invention. The embodiments and features in the embodiments of the present application can be arbitrarily combined with each other without conflict. The protection scope of the present invention shall be the technical solutions recorded in the claims, including equivalent replacement solutions of the technical features in the technical solutions recorded in the claims. That is, equivalent replacement improvements within this scope are also within the protection scope of the present invention.
Claims
1. A method for preparing a mixed positive electrode for a solid-state battery, characterized in that: The synthesis method comprises the following steps: (1) selecting an iodine-containing material A1 and a lithium battery positive electrode material A2 with a predetermined content; A1 and A2 are mixed to obtain mixed material A; (2) grinding the mixture A in an agate mortar and mixing it uniformly to form fine particles to obtain a mixed material C; (3) Grinding the mixed material C, the conductive agent D, the binder E, and the solvent F in a ball mill to obtain a mixed slurry G; (4) coating the mixed slurry G on the carbon-coated aluminum foil, with the coating thickness being 10-100 μm; (5) Drying the coated aluminum foil in a vacuum environment at a drying temperature of 50-110° C. to obtain an iodine-added mixed positive electrode.
2. The method for preparing a hybrid positive electrode for a solid-state battery according to claim 1, characterized in that: The iodine-containing material A1 is one or more of methylamine hydroiodide, tetrabutylammonium triiodide, imidazole hydroiodide, 1-iodoferrocene, iodinated polyacrylonitrile, lithium iodide, sodium iodide, potassium iodide, and methyl iodide; the lithium battery positive electrode material A2 is one or more of lithium iron phosphate, lithium manganese iron phosphate, lithium nickel cobalt manganate, lithium manganate, etc.; the mass ratio of the iodine-containing material A1 to the lithium battery positive electrode material A2 is 0.1~10.
3. The method for preparing a hybrid positive electrode for a solid-state battery according to claim 1, characterized in that: The grinding time in step (2) is 1-6 hours, the grinding time in step (3) is 1-6 hours, and the drying time in step (5) is 6-12 hours.
4. The method for preparing a hybrid positive electrode for a solid-state battery according to claim 1, characterized in that: The conductive agent is one or more of graphite, carbon nanotubes, acetylene black and graphene.
5. The method for preparing a hybrid positive electrode for a solid-state battery according to claim 1, characterized in that: The binder E in step (3) is one or more of polyvinylidene fluoride, styrene-butadiene rubber, carboxymethyl cellulose, polyacrylic acid, polyacrylonitrile and polyacrylate.
6. The method for preparing a hybrid positive electrode for a solid-state battery according to claim 1, characterized in that: The solvent is one or more of N,N-dimethylformamide, acetonitrile, tetrahydrofuran, ethylene glycol dimethyl ether, N-methyl pyrrolidone, anisole, dimethyl sulfoxide, and acetone.
7. The method for preparing a mixed positive electrode for a solid-state battery according to claim 1, characterized in that: The mass ratio of the mixed material C, the conductive agent D, and the binder E described in step (1) is 8:1:
1.
8. A hybrid positive electrode for a solid-state battery, characterized in that: The method is prepared by the method according to any one of claims 1 to 7.
9. A battery, characterized in that: The battery comprises the mixed positive electrode as claimed in claim 8 and a negative electrode composed of lithium metal and a polyethylene oxide solid electrolyte.
10. The battery according to claim 9, characterized in that: The test voltage range is 2.0~3.8V, and it can be stably cycled for at least 1000 times at a high rate of 2C, and can achieve a high surface capacity of 5.6 mgcm -2 And run stably for at least 50 cycles at 0.5C rate.
Citation Information
Patent Citations
Positive electrode composite material of lithium ion battery and all-solid-state battery containing the same
CN109449414A
Manufacturing method of solid-state battery containing flexible composite solid-state positive pole piece and solid-state battery
CN117423906A
Method for recycling and regenerating retired ternary lithium battery by using eutectic solvent
CN118315708A
Preparation method and application of iodide additive-introduced composite sulfur positive electrode
CN118630131A
Sulfur-based positive electrode active material for use in solid-state battery, preparation for material, and applications thereof
US20210175494A1
